Answer:
We are given the function h(y) = 4|y + 2| - 3
So, to get the value of h(-8), we just have to replace the y in the equation with -8
In functions, the variable in the parentheses next to the name of the function is the variable we have to replace since the function is defined in the terms of that one variable. When you do more advanced questions, you will encounter functions with more than 1 variable
h(y) = 4 | y + 2 | - 3
replacing y with -8 to get the output in terms of -8
h(-8) = 4 | -8 + 2 | -3
h(-8) = (4 * 6) - 3
h(-8) = 24 - 3
h(-8) = 21